2001
DOI: 10.1248/cpb.49.305
|View full text |Cite
|
Sign up to set email alerts
|

Dimer and Superstructure of the Active Form of a Vitamin D3. 1.ALPHA.,24(R)Dihydroxy-vitamin D3 Monohydrate, C27O3H44 H2O.

Abstract: The structure of vitamin D was first analyzed on calciferol by heavy atom method in 1948.2) In 1977, 25-hydroxy-vitamin D 3 (25(OH)-VD 3 ) was solved by direct method precisely.3) Until the analysis of calcipotriol mono-hydrate in 1993, 4) the active form of vitamin D 3 in which the hydroxyl group is replaced at the 1a position by metabolism was not analyzed. Calcipotriol is a 1,24(R)(OH) 2 -type VD 3 , and has a rigid chain with a double bond and a terminal three-membered ring. In 1996, 1,25(OH) 2 -VD 3 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…30 This fact could, in turn, decrease the ability of the synthesized analogue to bind VDR and affect its biological activity. Literature data prove that the natural hormone 31 and the vast majority of other 1α-hydroxylated vitamin D compounds adopt in the crystalline state exclusively the β-form of their A rings (with an exception of tacalcitol monohydrate 32 and calcipotriol anhydrate 33 ) characterized by equatorial and axial disposition of 1α-and 3β-hydroxyls, respectively, whereas the 5,7-diene fragment of their B-seco rings is almost planar. Crystallographic data from the growing number of solved crystalline complexes of the vitamin D receptor (VDR) and vitamin D analogues 34 indicate the s-trans conformation of the ligand's intercyclic C(5)C(6)−C( 7)C(8) diene moiety, exhibiting a torsion angle of ca.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 This fact could, in turn, decrease the ability of the synthesized analogue to bind VDR and affect its biological activity. Literature data prove that the natural hormone 31 and the vast majority of other 1α-hydroxylated vitamin D compounds adopt in the crystalline state exclusively the β-form of their A rings (with an exception of tacalcitol monohydrate 32 and calcipotriol anhydrate 33 ) characterized by equatorial and axial disposition of 1α-and 3β-hydroxyls, respectively, whereas the 5,7-diene fragment of their B-seco rings is almost planar. Crystallographic data from the growing number of solved crystalline complexes of the vitamin D receptor (VDR) and vitamin D analogues 34 indicate the s-trans conformation of the ligand's intercyclic C(5)C(6)−C( 7)C(8) diene moiety, exhibiting a torsion angle of ca.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The residue was purified by flash chromatography (SiO 2 , 0.5% Et 2 O/hexanes) to afford nitrile 29 (490 mg, 95%, colorless oil, contaminated with ca. 20% of its 4′Z-isomer): 1 H NMR (200 MHz, CDCl 3 ) δ 2.99 (1H, dm, J ∼ 13.0 Hz), 1.98 (3H, br s), 1.19 (6H, s), 0.94 (9H, t, J = 8.0 Hz), 0.94 (3H, d, J ∼ 6 Hz), 0.67 (3H, s), 0.56 (6H, q, J = 8.0 Hz); minor 4′Z-isomer: δ (selected signals) 2.64 (m); 13 2-[(1′R,3a′R,7a′R)-1′-[(R)-1″,5″-Dimethyl-5″-[(triethylsilyl)oxy]hexyl]-7a′-methyloctahydro-inden-(4′E)-ylidene]-propionaldehyde (32). A solution of diisobutylaluminum hydride in toluene (2.25 mL, 1 M, 2.25 mmol) was added to a stirred solution of nitrile 29 (487 mg, 1.13 mmol) in dry toluene/CH 2 Cl 2 (2:1, 15 mL) at −78 °C under argon.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Contrary to the plain vitamin D 3 and its circulating metabolite (25‐OH‐D 3 ,, both lacking 1α‐hydroxyl, 1,25‐(OH) 2 D 3 trihydrate exists in the solid state exclusively in the β‐form . Surprisingly, the natural precursor of the final metabolite of vitamin D 3 (tacalcitol, 1,24‐dihydroxyvitamin D 3 ) was found to exist as a monohydrate in the solid state in the α‐form, as the only analog of 1,25‐(OH) 2 D 3 that exists in the solid state in this conformation. The latest finding is not in favor with the early considerations in this field and posterior hypothesis that vitamins D adopt the β‐form of A‐ring during the interaction with their receptor.…”
Section: Introductionmentioning
confidence: 95%
“…Analysis of the results showed that the chair β-conformation was required for binding . Until now, the only known examples of the chair α-conformation in the crystal lattice were the monohydrate of (24 R )-1,24-dihydroxyvitamin D 3 (tacalcitol) and 7-methyl-1α,25-(OH) 2 -19- nor -D 3 . Moreover, several examples of vitamin D 3 adopting a chair α-conformation have been described along with an example of the anhydrous form of calcipotriol also adopting both α- and β-conformations.…”
Section: Introductionmentioning
confidence: 99%